The impact of SLCO1B1 genetic polymorphisms on neonatal hyperbilirubinemia: a systematic review with meta-analysis - Jiebo Liu; Jun Long; Shaofang Zhang; Xiaoyan Fang; Yuyuan Luo (Brazilian Society of Pediatrics, 2013)
Objective: To determine whether three variants (388 G>A, 521 T>C, and 463 C>A) of the solute carrier organic anion transporter family member 1B1 (SLCO1B1) are associated with neonatal hyperbilirubinemia. Data source: The China National Knowledge Infrastructure and MEDLINE databases were searched. The systematic review with meta-analysis included genetic studies which assessed the association between neonatal hyperbilirubinemia and 388 G>A, 521 T>C, and 463 C>A variants of SLCO1B1 between January of 1980 and December of 2012. Data selection and extraction were performed independently by two reviewers. Summary of the findings: Ten articles were included in the study. The results revealed that SLCO1B1 388 G>A is associated with an increased risk of neonatal hyperbilirubinemia (OR, 1.39; 95% CI, 1.07-1.82) in Chinese neonates, but not in white, Thai, Latin American, or Malaysian neonates. The SLCO1B1 521 T>C mutation showed a low risk of neonatal hyperbilirubinemia in Chinese neonates, while no significant associations were found in Brazilian, white, Asian, Thai, and Malaysian neonates. There were no significant differences in SLCO1B1 463 C>A between the hyperbilirubinemia and the control group. Conclusion: This study demonstrated that the 388 G>A mutation of the SLCO1B1 gene is a risk factor for developing neonatal hyperbilirubinemia in Chinese neonates, but not in white, Thai, Brazilian, or Malaysian populations; the SLCO1B1 521 T>C mutation provides protection for neonatal hyperbilirubinemia in Chinese neonates, but not in white, Thai, Brazilian, or Malaysian populations.